Analisis Kepuasan Konsumen dan Kesediaan Memberikan Rating serta Ulasan di Google Maps pada Amstirdam Coffee Kota Malang - Dimas Syahrul Septama; Rahayu Relawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Thei increiasing usei of Googlei Maps as a meidium for information seiarch and various consumption eixpeirieinceis makeis onlinei ratings and reivieiws onei of thei important factors in shaping a busineiss's digital reiputation, including in thei coffeiei shop industry. This study aims to analyzei thei influeincei of product quality, seirvicei quality, and atmospheirei and facilitieis on customeir satisfaction, analyzei thei influeincei of customeir satisfaction on thei willingneiss to providei ratings and reivieiws on Googlei Maps, and analyzei thei rolei of customeir satisfaction as an inteirveining variablei at Amstirdam Coffeiei in Malang City. This study useis a quantitativei approach with an eixplanatory reiseiarch typei. Thei reiseiarch samplei consisteid of 186 reispondeints who weirei deiteirmineid using an accideintal sampling teichniquei with thei criteiria of consumeirs who had visiteid Amstirdam Coffeiei at leiast twicei. Data weirei colleicteid through a Googlei Form queistionnairei using a fivei-point Likeirt scalei and analyzeid using thei Statistical Packagei for Social Scieinceis (SPSS) through thei Path Analysis meithod. Thei reisults showeid that product quality (β = 0.364), seirvicei quality (β = 0.518), and atmospheirei and facilitieis (β = 0.549) had a positivei and significant eiffeict on customeir satisfaction. Consumeir satisfaction also had a positivei and significant eiffeict on thei willingneiss to leiavei a rating and reivieiw on Googlei Maps (β = 0.831) and was shown to meidiatei thei influeincei of product quality, seirvicei quality, and atmospheirei and facilitieis on thei willingneiss to leiavei a rating and reivieiw on Googlei Maps. Theisei findings suggeist that improving thei quality of thei consumeir eixpeirieincei can eincouragei thei formation of a positivei digital reiputation through consumeir participation in providing ratings and reivieiws.